Integration of High‐k Oxide on MoS2 by Using Ozone Pretreatment for High‐Performance MoS2 Top‐Gated Transistor with Thickness‐Dependent Carrier Scattering Investigation. Issue 44 (1st October 2015) - Wang, Jingli; Li, Songlin; Zou, Xuming; Ho, Johnny; Liao, Lei; Xiao, Xiangheng; Jiang, Changzhong; Hu, Weida; Wang, Jianlu; Li, Jinchai
Abstract : A top‐gated MoS2 transistor with 6 nm thick HfO2 is fabricated using an ozone pretreatment. The influence to the top‐gated mobility brought about by the deposition of HfO2 is studied statistically, for the first time. The top‐gated mobility is suppressed by the deposition of HfO2, and multilayered samples are less susceptible than monolayer ones.